Exploring research potential: Bologna reform and Europeanisation beyond the European Union in the case of Norway - Iryna Kushnir (University of Aberdeen, School of Education, 2016)
The aim of this article is to explore research potential of the theme: the role of the Bologna reform in the Europeanisation beyond the European Union (EU) in the case of Norway. The investigation of such potential is conducted through a relevant literature review and the identification of research questions that have not yet been addressed in the literature. This article serves as an important step towards developing a proposal for future research in this area.